IMPLIKASI HUKUM BAGI NOTARIS YANG TIDAK MELEKATKAN SIDIK JARI PENGHADAP PADA MINUTA AKTA - Arief Rahman Mahmoud (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract __________________________________________________________________ Â This writing aims to determine what is the background of the acknowledgement of fingerprint into Certificate Minute and legal implication to Notary Officer who does not acknowledge fingerprint, by using the method of normative legal research, law approach, to obtain the views and doctrine as the basis for a legal argument over legal issues investigated. Based on the result of this examine and analysis,acknowledgement of fingerprint into Certificate Minute of Notary Public is aimed to anticipate the denial of applicant againts the signature in the Certificate Minute and therefore, fingerprint of the applicant is adhered as supplementary evidence.legal implication to Notary Officer who does not acknowledge applicant fingerprint into Certificate Minute is legal sanction based on Article 16 Verse (11) of Notary Title Act, which includes (a) written reprimand, (b) temporary suspension, (c) officially dismissal, and (d) unofficial dismissal. If written reprimand is not respected or there is additional deviation, Notary Officer can be subjected to the subsequent stratified sanction. Key words: notary, fingerprint, applicant, certificate minute Â Abstrak __________________________________________________________________ Tulisan ini bertujuan untuk mengetahui latar belakang dilekatkannya sidik jari penghadap pada Minuta Akta dan implikasi hukum bagi Notaris yang tidak melekatkannya, dengan menggunakan metode normatif legal research, melalui pendekatan undang-undang guna memperoleh pandangan dan doktrin sebagai dasar argumentasi hukum atas isu hukum yang diteliti. Berdasar hasil penelitian diketahui bahwa latar belakang dilekatkan sidik jari penghadap pada Minuta Akta bertujuan untuk mengantisipasi apabila para penghadap menyangkal tanda tangannya, maka sebagai bukti tambahan digunakan sidik jari penghadap tersebut. Implikasi hukum bagi Notaris yang tidak melekatkan sidik jari penghadap pada Minuta Akta dapat dikenai sanksi sesuai Pasal 16 ayat (11) Undang-Undang Jabatan Notaris berupa: (a)peringatan tertulis; (b)pemberhentian sementara; (c)pemberhentian dengan hormat; (d)pemberhentian dengan tidak hormat. Jika sanksi peringatan tertulis kepada Notaris tidak dipatuhi atau terjadi pelanggaran oleh Notaris yang bersangkutan, maka dapat dijatuhi sanksi berikutnya secara berjenjang. Kata kunci: notaris, sidik jari, penghadap, minuta akta